In-Hospital cardiac arrest complicating ST-elevation myocardial Infarction: Temporal trends and outcomes based on management strategy. (May 2023) - Bhat, Anusha G; Verghese, Dhiran; Harsha Patlolla, Sri; Truesdell, Alexander G; Batchelor, Wayne B; Henry, Timothy D; Cubeddu, Robert J; Budoff, Matthew; Bui, Quang; Matthew Belford, Peter; X Zhao, David; Vallabhajosyula, Saraschandra
Abstract: Background: There are limited data on the relationship of ST-segment-elevation myocardial infarction (STEMI) management strategy and in-hospital cardiac arrest (IHCA). Aims: To investigate the trends and outcomes of IHCA in STEMI by management strategy. Methods: Adult with STEMI complicated by IHCA from the National Inpatient Sample (2000–2017) were stratified into early percutaneous coronary intervention (PCI) (day 0 of hospitalization), delayed PCI (PCI ≥ day 1), or medical management (no PCI). Coronary artery bypass surgery was excluded. Outcomes of interest included in-hospital mortality, adverse events, length of stay, and hospitalization costs. Results: Of 3, 967, 711 STEMI admissions, IHCA was noted in 102, 424 (2.6%) with an increase in incidence during this study period. Medically managed STEMI had higher rates of IHCA (3.6% vs 2.0% vs 1.3%, p  < 0.001) compared to early and delayed PCI, respectively. Revascularization was associated with lower rates of IHCA (early PCI: adjusted odds ratio [aOR] 0.44 [95% confidence interval (CI) 0.43–0.44], p  < 0.001; delayed PCI aOR 0.33 [95% CI 0.32–0.33], p  < 0.001) compared to medical management. Non-revascularized patients had higher rates of non-shockable rhythms (62% vs 35% and 42.6%), but lower rates of multiorgan damage (44% vs 52.7% and 55.6%), cardiogenic shock (28% vs 65% and 57.4%) compared to early and delayed PCI, respectively (all p  < 0.001). In-hospital mortality was lower with early PCI (49%, aOR 0.18, 95% CI 0.17–0.18), and delayed PCI (50.9%, aOR 0.18, 95% CI 0.17–0.19) ( p  < 0.001) compared to medical management (82.5%). Conclusion: Early PCI in STEMI impacts the natural history of IHCA including timing and type of IHCA.